2019
DOI: 10.26492/gbs71(2).2019-12
|View full text |Cite
|
Sign up to set email alerts
|

Free radical scavenging effects of the Philippine endemic medicinal plant Alpinia elegans (Zingiberaceae)

Abstract: Alpinia elegans (C.Presl) K.Schum. is an endemic Philippine medicinal plant used in the treatment of various conditions such as muscoloskeletal diseases, hemoptysis, headache, migraine, stomach ache, and as an anti-relapse for women. The major phytochemical constituents of the ethanolic extract from the leaves of Alpinia elegans were screened and their antioxidant activity was evaluated using an in vitro 1,1-Diphenyl-2-picrylhydrazyl (DPPH) free radical-scavenging (antioxidant) activity assay. Flavonoids, ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…elegans had a 100% FL value with a high UR value used distinctly by both tribes for fevers, indicating high agreement for its utility with high respondent confidence. A. elegans contain essential oils that exhibit medicinal properties such as cytotoxins, antioxidants, and some antimicrobial activity (Houdkova et al 2018;Naive et al 2019). The Alpinia genus has been used in traditional medicine to achieve anti-inflammatory, bacteriostatic, fungistatic, antitumor, and antiviral effects (Zoghbi 1999;Corbi et al 2006;Upadhyay et al 2011;Nguyen et al 2014) The leaves were the most frequently used plant part for both tribes.…”
Section: Discussionmentioning
confidence: 99%
“…elegans had a 100% FL value with a high UR value used distinctly by both tribes for fevers, indicating high agreement for its utility with high respondent confidence. A. elegans contain essential oils that exhibit medicinal properties such as cytotoxins, antioxidants, and some antimicrobial activity (Houdkova et al 2018;Naive et al 2019). The Alpinia genus has been used in traditional medicine to achieve anti-inflammatory, bacteriostatic, fungistatic, antitumor, and antiviral effects (Zoghbi 1999;Corbi et al 2006;Upadhyay et al 2011;Nguyen et al 2014) The leaves were the most frequently used plant part for both tribes.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of data on antioxidant potential of EOs obtained from the abovementioned plant species with the exception of C. iners leaf oil that was observed to possess antioxidant effect with IC 50 value of 218.88 µg/mL [ 45 ]. Other study has previously reported DPPH radical scavenging activity of ethanol extract from A. elegans leaves with IC 50 value of 97.58 µg/mL [ 46 ]. However, EOs of these both species did not produce any activity in our study.…”
Section: Discussionmentioning
confidence: 99%